Contemporary challenges of the regulation of religions in Europe (2023), de Helena Vilaça, Maria João Oliveira and Anne-Laure Zwilling (coord.). - Leão, Anabela Costa (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2025)
.